Condensation of 4-amino-3-(2-methoxy-4-propylphenoxymethylene)-(1H)-1,2,4-triazole-5-thione with some aromatic aldehydes - Dinh, Nguyen Huu; Hien, Nguyen (Vietnam Journal of Chemistry, 2014)
4-Amino-3-(2-methoxy-4-propylphenoxymethylen)-(1H)-1,2,4-triazole-5-thione was prepared from eugenol in Ocimum Sanetum L. essential oil. A series of 7 imines were synthesized from these key compounds by condensing it with different aromatic aldehydes. The structures of these imines were confirmed by EI MS, IR and NMR spectroscopy, in many cases 2D NMR spectra are also used.